Developing technology-based interventions for infectious diseases: ethical considerations for young sexual and gender minority people - Cascalheira, Cory J.; Pugh, Tyler H.; Hong, Chenglin; Birkett, Michelle; Macapagal, Kathryn; Holloway, Ian W. (Frontiers in Reproductive Health, 2023)
Compared to their heterosexual and cisgender peers, young sexual and gender minority (YSGM) people are more likely to contract sexually transmitted infections (STIs; e.g., HIV) and to face adverse consequences of emerging infections, such as COVID-19 and mpox. To reduce these sexual health disparities, technology-based interventions (TBIs) for STIs and emerging infections among YSGM adolescents and young adults have been developed. In this Perspective, we discuss ethical issues, ethical principles, and recommendations in the development and implementation of TBIs to address STIs and emerging infections among YSGM. Our discussion covers: (1) confidentiality, privacy, and data security (e.g., if TBI use is revealed, YSGM are at increased risk of discrimination and family rejection); (2) empowerment and autonomy (e.g., designing TBIs that can still function if YSGM users opt-out of multiple features and data collection requests); (3) evidence-based and quality controlled (e.g., going above and beyond minimum FDA effectiveness standards to protect vulnerable YSGM people); (4) cultural sensitivity and tailoring (e.g., using YSGM-specific models of prevention and intervention); (5) balancing inclusivity vs. group specificity (e.g., honoring YSGM heterogeneity); (6) duty to care (e.g., providing avenues to contact affirming healthcare professionals); (7) equitable access (e.g., prioritizing YSGM people living in low-resource, high-stigma areas); and (8) digital temperance (e.g., being careful with gamification because YSGM experience substantial screen time compared to their peers). We conclude that a community-engaged, YSGM-centered approach to TBI development and implementation is paramount to ethically preventing and treating STIs and emerging infections with innovative technology.